PERAN KOMPETENSI SUMBER DAYA MANUSIA DALAM MEMODERASI HUBUNGAN PEMANFAATAN TEKNOLOGI INFORMASI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN LPD SE-KECAMATAN PENEBEL - Ni Komang Desi Lestari; Ni Putu Ayu Kusumawati; I Putu Nuratama (Hita Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of the utilization of information technology and internal control systems on the quality of financial reports and to determine the role of human resource competence in moderating the relationship between the utilization of information technology and internal control systems on the quality of financial reports at the Village Credit Institution (LPD) in Penebel District. The population in this study were 50 LPDs in Penebel District with 140 respondents consisting of the Head of the LPD and the LPD Internal Supervisory Board. The sampling technique used in this study is saturated sampling technique so that the entire population is used as a sample, namely the sample obtained in this study was 140 respondents. The data analysis technique used in this research is Descriptive Statistical Test and Partial Least Square (PLS) analysis. The results of this study indicate that the utilization of information technology has a negative and insignificant effect on the quality of financial reports, while the internal control system has a positive and significant effect on the quality of financial reports and the interaction of human resource competence with the utilization of information technology has a positive and insignificant effect on the quality of financial statements and the interaction of human resource competence with the internal control system has a negative and insignificant effect on the quality of financial reports.